Antecedents and Consequences of Implementation Work From Home Policy At The Foreign Investment Tax Service Office One In South Jakarta - Rany Sangadji; Amir Fikri; Zainur Hidayah (Business and Entrepreneurial Review, 2022)
This research was motivated by the instructions to work, study and worship at home during the COVID-19 Pandemic. State Civil Administration (ASN) are instructed to work at home or later called Work From Home (WFH). The application of the WFH concept has a fairly high level of flexibility. The types of work for ASN that are excluded from carrying out the flexible concept are jobs that are directly related to service users, both the community and other stakeholders. WFH implementation does not always go well, the emergence of a cultural shock to the use of technology, the responsibility to manage household activities that can affect the stress level of employees, as well as disturbances from family members and other problems that occur at home lead to the inability of employees to concentrate while working at home which will effect on employee performance. The Foreign Investment Tax Service Office One (KPP PMA Satu) routinely performs periodic performance measurements. Performance measurement is carried out using the Balanced Scorecard (BSC) strategy. The Organizational Performance Value (NKO) of KPP PMA Satu in 2020 has decreased compared to 2019. Several factors that influenced the decline in NKO were the uncertain global economic conditions due to the pandemic and various online services. This research was conducted at KPP PMA Satu using 6 (six) variables with the aim of knowing the factors that influence the implementation of the WFH policy and the effect of the implementation of the WFH policy on the performance of KPP PMA Satu employees. The number of samples used are 111 employees who implement the WFH policy. The research method used is quantitative with a causal approach where the data obtained is processed using the Structural Equation Modeling (SEM) method. The results obtained are that work from home has a significant effect on employee performance.